The Princes from Kaptol : (Iron Age Burial Mounds in Papuk Geopark) - Potrebica, Hrvoje (2012)
he occurrence of a large and prosperous fortified settlement, rich grave goods from elite burials, which include exclusive and prestigious goods from distant areas, highlight the immense scientific and cultural potential of Kaptol in the Požega Valley (Croatia), as one of the most important Central European Early Iron Age sites.This is why the southernmost cultural group of the Hallstatt Cultural Complex was named after this site. The earth mounds covered wooden chambers surrounded by drystone walls, containing rich cremation burials. Sometimes these constructions reached monumental proportions with long ceremonial passages. Fewer than 20 of these monuments, reserved for the Early Iron Age elite, are known in continental Europe, and one of the largest and probably the best preserved was discovered a few years ago in Kaptol. The power and glory of Kaptol warrior-princes was primarily reflected in their weapons: spears, axes, whetstone-sceptres (a status symbol in Balkans area), as well as horse equipment, a universal status symbol of the ruling warrior class in the Hallstatt Culture. The extreme importance of Kaptol became obvious following the discovery of two princely graves with unique sets of defensive weapons. Among other luxurious items they contained two Greek helmets, the northernmost finds of Greek helmets in Europe! One of the most important graves from the Hallstatt culture was discovered in 2005 revealing almost thirty richly ornamented pottery vessels as well as bronze situla(bucket shaped containers) andarmourincluding a burned bowl-shaped helmet and the hub-cubs from the wheels of achariot! However, the most astonishing finds were two rich sets of weapons: spears, battle axes, extremely rare swords together with equipment for horses. The unique shapes and exquisitely decorated pottery, such as pots with bull-head decorations discovered at Kaptol, are defining characteristics of the Kaptol Group of the Halstatt culture during the Early Iron Age in central Europe. Most of the fine pottery is coated with graphite which gives them a special metallic sheen. One of the important sources of wealth and power of the Kaptol princes must have been the graphite mines which were still active in the mid-20th century.